High Concentration of Barium Sulfate for Scattering Strength Improvement to Achieve Better Color Uniformity of a WLED - Dung, Nguyen Van; Le, Anh-Tuan (Science and Technology Indonesia, 2025)
This simulation study provides a comprehensive investigation into the influence of varying concentrations of barium sulfate (BaSO4) on the optical characteristics of white light-emitting diodes (WLEDs). The research is conducted through MATLAB-based simulations that employ Mie-scattering theory to accurately model light–particle interactions. BaSO4 is chosen as a scattering medium due to its well-documented advantages, including chemical stability, non-toxicity, cost-effectiveness, and exceptionally high reflectivity across the visible spectrum. These properties make it a promising candidate for improving both the efficiency and the optical quality of WLEDs. In this study, BaSO4 particles are introduced into the WLED structure with the goal of enhancing two key performance metrics: color uniformity and luminous output. Through systematic modeling, scattering efficiencies are calculated at a range of BaSO4 concentrations to evaluate how particle density influences light propagation and distribution within the device. The results demonstrate a clear correlation between increasing BaSO4 concentration and improved scattering efficiency, leading to higher lumen output. However, the findings also indicate that performance gains reach an optimum at specific concentration levels, beyond which excessive scattering may reduce efficiency by causing unwanted light losses. Beyond luminous efficiency, the integration of BaSO4 also contributes positively to the color rendering capability of the WLED, minimizing color deviation and producing a more uniform and natural white emission. This highlights BaSO4’s dual role in enhancing both brightness and optical quality. Collectively, the outcomes of this simulation study emphasize the potential of BaSO4 as a functional scattering additive that can significantly improve WLED design. The insights gained offer valuable guidance for the development of next-generation solid-state lighting devices with superior optical performance, energy efficiency, and color stability.